Numerical study of advanced dispersion models in particle-laden swirling flows. (April 2018) - Kazemi, S.; Adib, M.; Amani, E.
Highlights: Advanced dispersion models are evaluated for particle-laden swirling flows. Without dispersion modeling, the correct particle-vortex interaction is not captured. Advanced PDF and MOB models perform well in the prediction of particle statistics. MOB is the most accurate model in predicting the cross-stream particle velocity fluctuations. Particle concentration is the most sensitive parameter to the choice of dispersion model. Abstract: In this study, the dispersion phenomenon in a poly-dispersed gas-solid confined swirling jet is investigated numerically using an Eulerian–Lagrangian framework. Three continuous random walk models, including Sommerfeld's model, Moissette et al. (MOB) model, and probability density function (PDF), and the conventionally used eddy life time (ELT) model are incorporated and compared. The results manifest that the important features of the flow, such as the penetration of the medium-sized particles into the corner recirculation zone and the distribution of the light particles downstream of the internal recirculation zone, can only be captured by a proper dispersion modeling even in an unsteady URANS approach resolving the precessing vortex core. Moreover, the ELT model has the largest errors for all particle statistics, especially for the fluctuating velocities (about 60% in average) while other models, especially MOB and PDF, bring about a satisfactory agreement with the experiment. MOB is the most accurate model in predicting the cross-stream particle velocity fluctuations with less than 20% error. Finally, for such a complex practical flow, the spatial decay of concentration profile is a key factor which is much more sensitive to the choice of dispersion model than the mean and fluctuating velocities.